Accumulation in an African Periphery A Theoretical Framework - Shivji, G.; Shivji, G. (Mkuki na Nyota Publishers, 2009)
The "Washington consensus" which ushered in neo-liberal policies in Africa is over. It was buried at the G20 meeting in London in early April, 2009. The world capitalist system is in shambles. The champions of capitalism in the global North are rewriting the rules of the game to save it. The crisis creates an opening for the global South, in particular Africa, to refuse to play the capitalist-imperialist game, whatever the rules. It is time to rethink and revisit the development direction and strategies on the continent. This is the central message of this intensely argued book. Issa Shivji demonstrates the need to go back to the basics of radical political economy and ask fundamental questions: who produces the society's surplus product, who appropriates and accumulates it and how is this done. What is the character of accumulation and what is the social agency of change? The book provides an alternative theoretical framework to help African researchers and intellectuals to understand their societies better and contribute towards changing them in the interest of the working people.